Switching the Reactivity of Palladium Diimines with "Ancillary" Ligand to Select between Olefin Polymerization, Branching Regulation, or Olefin Isomerization. Issue 3 (9th November 2020) - Jones, Glen R.; Basbug Alhan, Hatice E.; Karas, Lucas J.; Wu, Judy I.; Harth, Eva
Abstract: Coordinating solvents are commonly employed as ancillary ligands to stabilize late transition metal complexes and are conventionally considered to have little effect on the reaction products. Our work identifies that the presence of ancillary ligand in Pd‐diimine catalyzed polymerizations of α‐olefins can drastically alter reactivity. The addition of different amounts of acetonitrile allows for switching between distinct reaction modes: isomerization–polymerization with high branching (0 equiv.), regular chain‐walking polymerization (1 equiv.), and alkene isomerization with no polymerization (>20 equiv.). Optimization of the isomerization reaction mode led to a general set of conditions to switch a wide variety of diimine complexes into efficient alkene isomerization catalysts, with catalyst loading as low as 0.005 mol %. Abstract : The ancillary ligand often added to stabilize late transition metal catalysts for olefin polymerization actually has a profound effect on the reactivity of such complexes. We demonstrate that Pd‐ diimine catalysts can be switched between 3 reactions modes simply by varying the amount of ancillary ligand added to give either: isomerization‐polymerization (0 equiv.), regular polymerization (1 equiv.) or alkene isomerization (>20 equiv.)